2015
DOI: 10.1002/bit.25862
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of nitrate reductase alters metabolic branching of carbohydrate fermentation in the cyanobacterium Synechococcus sp. strain PCC 7002

Abstract: To produce cellular energy, cyanobacteria reduce nitrate as the preferred pathway over proton reduction (H2 evolution) by catabolizing glycogen under dark anaerobic conditions. This competition lowers H2 production by consuming a large fraction of the reducing equivalents (NADPH and NADH). To eliminate this competition, we constructed a knockout mutant of nitrate reductase, encoded by narB, in Synechococcus sp. PCC 7002. As expected, ΔnarB was able to take up intracellular nitrate but was unable to reduce it t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Owing to their ease of genetic modification, many cyanobacteria have been engineered to improve CO 2 capture and light utilization (Ducat et al, 2011; Lan and Liao, 2012; Yu et al, 2013). The capacity to improve these functions depends on how rapidly and completely the downstream steps can utilize the primary metabolic intermediates, thus fundamental studies are needed to understand key metabolic chokepoints and regulatory sites in carbon and energy metabolism (Krishnan et al, 2015b; Qian et al, 2015; Zhang et al, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…Owing to their ease of genetic modification, many cyanobacteria have been engineered to improve CO 2 capture and light utilization (Ducat et al, 2011; Lan and Liao, 2012; Yu et al, 2013). The capacity to improve these functions depends on how rapidly and completely the downstream steps can utilize the primary metabolic intermediates, thus fundamental studies are needed to understand key metabolic chokepoints and regulatory sites in carbon and energy metabolism (Krishnan et al, 2015b; Qian et al, 2015; Zhang et al, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…Nitrogen is essential for protein synthesis and urea allows cells to redirect saved equivalents to produce more proteins as reported (Qian et al, 2016). However, our results indicated that rising temperature caused negative effects on cellular proteins and ribosomal subunits in both nitrate-and urea-grown cells (Figures 4A,B and Table 1).…”
Section: Discussionmentioning
confidence: 91%
“…Ferredoxins are iron and sulfur-containing proteins that act as electron carriers during many important metabolic processes including oxidation-reduction, photosynthesis, and nitrogen fixation (Lea-Smith et al, 2016). More specifically, nitrate ferredoxin acts as a significant electron sink during the reversible, redox inter-conversion of nitrite to nitrate during photosynthesis (Flores et al, 2005;Qian et al, 2016).…”
Section: Lasso Regressionmentioning
confidence: 99%
“…NADPH dehydrogenases are among the top negative coefficients for all three flux datasets. Cyanobacteria consume a large amount of the cofactors NADPH and NADH whilst reducing nitrate to catabolize glycogen under dark anaerobic conditions (Qian et al, 2016). NADH dehydrogenase (type II) is a protein that catalyzes the electron transfer from NADH to a quinone molecule via a flavin co-factor (Heikal et al, 2014).…”
Section: Pearson Correlation Analysismentioning
confidence: 99%